2006
DOI: 10.1097/01.ftd.0000245771.82720.c7
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Inexpensive Method for Anticipating Severe Toxicity to Fluorouracil and Fluorouracil-based Chemotherapy

Abstract: Dihydropyrimidine dehydrogenase (DPD) deficiency leads to dramatic overexposure to fluorouracil (5-FU), resulting in a potentially lethal outcome in patients treated with standard doses. The aim of this study was to validate, in a routine clinical setting, a simple and rapid method to determine the DPD status in a subset of cancer patients, all presenting with life-threatening toxicities following 5-FU or capecitabine intake. In this study, 80 out of 615 patients (13%) suffered severe toxicities, including 5 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…ratio HPLC method in plasma. Both patients were found to be profoundly DPDdeficient with regard to our reference population [5]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ratio HPLC method in plasma. Both patients were found to be profoundly DPDdeficient with regard to our reference population [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Using this methodology, we found that this patient was profoundly DPD-deficient (Figure 1), with a U/UH2 ratio value of 3.6, i.e. more than 3-time higher than the mean values usually recorded in our reference population [5]. Owing to the severity of her DPD deficiency, treatment was definitively stopped.…”
Section: Case-reportsmentioning
confidence: 95%
See 2 more Smart Citations
“…Since eighties, the numerous methods based on determination of DPD status were advised to predict serious 5-FU-related toxicity. The function tests have been used for measurement of DPD enzyme activity by 2-[ 13 C]-uracil breath test, or determining uracil/dihydrouracil or [ 14 C]-thymine/dihydrothymine plasma ratio [32][33][34]. Substantial drawbacks of function tests are a need for specialized technology approaches or the use of radiolabeled chemicals not available worldwide [34].…”
Section: Discussionmentioning
confidence: 99%